A generalization of Pappus graph - Sucharita Biswas; Angsuman Das (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2022)
In this paper, we introduce a new family of cubic graphs Γ(m), called Generalized Pappus graphs, where m ≥ 3. We compute the automorphism group of Γ(m) and characterize when it is a Cayley graph.